Analysis of metallothioneins by mass spectrometry-based hyphenated techniques. Issue 2 (7th February 2016) - Hu, Bin; Peng, Lu; He, Man; Chen, Beibei
Abstract: As a kind of cysteine-rich protein, metallothioneins (MTs) play an important role in metal-related biochemical pathways, including homeostasis of essential metals, detoxification of heavy metals, and scavenging of free radicals. The analysis of MTs is challenging due to the complexity of the sample matrix, the coexisting isoforms, and easy destruction of the integrity of metal–MTs complexes during processing. Mass spectrometry (MS)-based hyphenated techniques, such as high-performance liquid chromatography (HPLC) or capillary electrophoresis (CE) combined with inductively coupled plasma (ICP)-MS or electrospray ionization (ESI)-MS have become the most effective methods for MT analysis because they can provide comprehensive information on MTs, including the amount, the metal components, and the isoforms. In this review, we summarize the analysis of MTs using MS-based hyphenated techniques. The use of ICP-MS and ESI-MS as well as matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF)-MS are stated. The combination of CE or HPLC with ICP-MS and ESI-MS for the analysis of MTs isoforms is discussed. Four HPLC separation modes, including size exclusion chromatography (SEC), anion-exchange chromatography (AEC), reversed phase liquid chromatography (RPLC), and hydrophilic interaction liquid chromatography (HILIC), are elaborated. The coupling of RPLC with ICP-MS and ESI-MS in parallel for the analysis of MT subisoforms is especially highlighted.